Effect of aggregate gradation on crack propagation in asphalt mixtures at low temperatures based on the Eshelby equivalent inclusion theory. (5th July 2021) - Du, Jianhuan; Ren, Dongya; Ai, Changfa; Zhang, Jiakang; Qiu, Yanjun
Highlights: Based on the Eshelby Equivalent Inclusion Theory, the changes in the time domain of the shear modulus and the energy release rate of asphalt mixtures can be calculated. The stress field in the crack tip region is identified using the FISH programming subroutine. A random growth algorithm has been used to established arbitrary shape of aggregate particles. Abstract: This paper presents a study to evaluate the mixed-mode crack propagation behavior of several typical asphalt mixtures at low temperatures. Based on the Eshelby equivalent inclusion theory and Griffith micro-fracture theory, the basis for determining the I-II mix mode fracture types during crack propagation was established. A random particle-based growth algorithm was adopted to develop a heterogeneous DEM model for three typical asphalt mixtures: open-graded structure (OGFC-13), gap-graded structure (SMA-13), and dense-graded structure (AC-13) mixtures, and a virtual indirect tensile test was conducted. The characteristics of the development of I-II mix mode fractures for three asphalt mixtures at low temperatures were analyzed in four aspects: changes in the number of micro-cracks, proportions of crack types, energy release rates, and force chain diagrams of crack tip stress fields. The results indicate that: (1) From the perspective of the changes in the number of cracks, the dense-graded asphalt mixture has the largest number of micro-cracks, and the proportion of mode I cracks that are mainly due to tension is dominant, while the proportion of mode II cracks that are mainly due to shear is insignificant; (2) The crack energy release rate G (t) in the time-domain increases as the rate of internal energy consumption increases, along with a reduction in the energy storage rate, as the spatial distribution of aggregates change in the open-graded, gap-graded, and dense-graded asphalt mixtures. From an energy standpoint, it was found that more energy is required when the dense-graded asphalt mixture is fractured; (3) In terms of the stress field distributions in the crack tip regions, compared with the open-graded and gap-graded asphalt mixtures, the interior of a dense-graded asphalt mixture is less likely to develop stress concentrations, which is beneficial in suppressing the occurrence of a shear stress field, thereby reducing the occurrence of mode II low-temperature cracks. The results of this research provide theoretical support for the anti-cracking design of asphalt mixtures based on meso -characteristics.